Productivity Of Oil Wells In Arbitrarily Shaped Reservoirs. - M.Nasir, Mohamad Ibrahim (2004)
A Boundary Element approach for predicting the productivity of oil wells arranged in complex configurations within irregularly shaped reservoirs were developed. The integral equations are written for boundary points as well as for the locations of the wells which are treated as point sources and sinks with specified pressures but unknown strengths.